2020
DOI: 10.1186/s12885-020-07039-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the oncogene LSF with either the small molecule inhibitor FQI1 or siRNA causes mitotic delays with unaligned chromosomes, resulting in cell death or senescence

Abstract: Background: The oncogene LSF (encoded by TFCP2) has been proposed as a novel therapeutic target for multiple cancers. LSF overexpression in patient tumors correlates with poor prognosis in particular for both hepatocellular carcinoma and colorectal cancer. The limited treatment outcomes for these diseases and disappointing clinical results, in particular, for hepatocellular carcinoma in molecularly targeted therapies targeting cellular receptors and kinases, underscore the need for molecularly targeting novel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 46 publications
(79 reference statements)
3
20
0
Order By: Relevance
“…In addition, cell blebbing was observed in the presence of FQI1 (see Supplementary Movies 1 and 2 ), which is consistent with activation of the myosin II pathway via the observed phosphorylation of MLC2. Since FQI1 can cause cells to undergo mitotic arrest 17 , 18 , which also results in cells “rounding-up”, although not as quickly, the cell cycle stage of cells exhibiting this compact phenotype was examined by cellular DNA profiling. By this analysis, there was no apparent shift in cell cycle phases upon such a short incubation with FQI1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cell blebbing was observed in the presence of FQI1 (see Supplementary Movies 1 and 2 ), which is consistent with activation of the myosin II pathway via the observed phosphorylation of MLC2. Since FQI1 can cause cells to undergo mitotic arrest 17 , 18 , which also results in cells “rounding-up”, although not as quickly, the cell cycle stage of cells exhibiting this compact phenotype was examined by cellular DNA profiling. By this analysis, there was no apparent shift in cell cycle phases upon such a short incubation with FQI1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether the novel phenotypic effects in FH-B and RPE cells are related to the previously described activities of FQI1 15 , 17 , we tested whether these phenotypes were replicated using a recently developed FQI family member, FQI2-34. FQI2-34 is more potent than FQI1, exhibiting 17-fold higher efficacy than FQI1 in inhibiting proliferation of FH-B cells (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of TFCP2 expression in liver cancer and expression of treatment-resistant and senescence-related gene have already been reported ( 27 ). Treatment of Hela cells with TFCP2 inhibitor FQI1 leads to polynuclear, apoptotic, and senescent Hela cells ( 22 ). These existing findings, plus our finding, further demonstrate the regulatory effect of TFCP2 on cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that treatment of glioma cells with HMGCR inhibitor statins can induce cell senescence ( 21 ). Currently, studies show that TFCP2 knockdown can induce the mitotic delay and senescence of Hela cells ( 22 ), but the mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%